2012
DOI: 10.1371/journal.pone.0039090
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod Regulates Corticosterone Rhythms by Altered Adrenal Sensitivity via Melatonin-Independent Mechanisms in Fischer 344 Rats and C57BL/6J Mice

Abstract: Most species living in temperate zones adapt their physiology and behavior to seasonal changes in the environment by using the photoperiod as a primary cue. The mechanisms underlying photoperiodic regulation of stress-related functions are not well understood. In this study, we analyzed the effects of photoperiod on the hypothalamic-pituitary-adrenal axis in photoperiod-sensitive Fischer 344 rats. We first examined how photoperiod affects diurnal variations in plasma concentrations of adrenocorticotropic hormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…The results regarding SOCS3 mRNA levels in the hypothalamus might also be a consequence of overfasting or the secondary effects of leptin. Alternately, these parameters might have diurnal variations that are regulated by photoperiod and/or fasting (19,23), and the sampling time point in this study might not detect the differences occurred at different time points.…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…The results regarding SOCS3 mRNA levels in the hypothalamus might also be a consequence of overfasting or the secondary effects of leptin. Alternately, these parameters might have diurnal variations that are regulated by photoperiod and/or fasting (19,23), and the sampling time point in this study might not detect the differences occurred at different time points.…”
Section: Methodsmentioning
confidence: 90%
“…In addition, rats under the LD condition exhibited lower levels of corticosterone, which is reported to increase body weight and leptin levels (13). Since leptin signaling system and plasma corticosterone levels have diurnal variations regulated by photoperiod and/or fasting (19,23), more frequent sampling time point throughout 24 h is needed to clarify the precise mechanisms. Nevertheless, it is of note that SOCS3 expression was higher with HFD feeding under the SD condition but not under the LD condition.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to ACTH challenge, blood was sampled at 0800 hours to establish a baseline level of CORT. Mice were then given an injection of dexamethasone (0.05 mg/kg) in order to limit endogenous ACTH release (Dijkstra et al, 1996;Han et al, 1998;Michopoulos et al, 2012;Otsuka et al, 2012). This dose of dexamethasone was chosen as it exhibited equivalent CORT suppression in both groups following peripheral administration in Experiment 2.…”
Section: Acth Challengementioning
confidence: 99%
“…As such, short day (SD) will be synonymous with autumn and winter months when daylight is typically less than 12 h. Long day (LD) will be used interchangeably with the summer months when daylight is typically more than 12 h. The general guiding behavioral principle is that during LD photoperiods, food intake is increased to accumulate fat and during SD photoperiods, there is a decrease in food intake and a utilization of the excess fat (Schuhler and Ebling, 2006). As an example, Otsuka and colleagues found that during SD conditions (winter), rats have a lower body weight and epididymis fat mass compared to rats exposed to LD (summer) conditions (Otsuka et al, 2012). We hypothesize that seasonal changes in the sensitivity to and circulating levels of glucocorticoids and the feeding-related hormones ghrelin and leptin may be contributing factors to these seasonal variations in food intake.…”
Section: General Overviewmentioning
confidence: 99%
“…In studies using rats and mice where light and dark cycles were manipulated to mimic winter (SD) and summer (LD) months, basal glucocorticoid levels tended to be higher during the SD periods (winter) than LD periods (summer) (Ottenweller et al, 1987; Pyter et al, 2007; Otsuka et al, 2012). When the photoperiod was manipulated in Syrian hamsters, they showed modification of plasma concentrations of glucocorticoids such that the peak level of circulating glucocorticoids during SD was lower compared to LD (Ottenweller et al, 1987).…”
Section: Glucocorticoidsmentioning
confidence: 99%